PELAKSANAAN PENGIKATAN JAMINAN FIDUSIA DALAM KREDIT PERBANKAN - Marita Widyasari Puspita, Ketut; Puspawati, I Gusti Ayu; -, Marwanto (Kertha Semaya : Journal Ilmu Hukum, 2014)
The term of Fiduciary has known in Article 1 paragraph 2 of Act 42 of 1999 about Fiduciary which says that Fiduciary is a guarantee of the moving objects, both tangible and intangible, as defined in Law Nomer 4 of 1996 about The Right Dependents, who remain in control of fiduciary giver, as collateral for the repayment of certain debts which gives precedence to the receiver position against other creditors fiduciary. Fiduciary shall be registered through the official Fiduciary registration office, which is The Ministry of Law and Human Rights. So the creditors whom be the first to register the fiduciary is the recipient which considered by the creditor are parties to the agreement fiduciary.
Keywords: Implementation, Fiduciary, Credit banking